2014
DOI: 10.3171/2013.11.jns131366
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and agreement in the management of unruptured intracranial aneurysms

Abstract: Object The management of unruptured intracranial aneurysms remains controversial. The goal of this study was to evaluate the clinical community agreement in decision making regarding unruptured intracranial aneurysms. Methods A portfolio of 41 cases of unruptured intracranial aneurysms with angiographic images, along with a short description of the patient presentation, was sent to 28 clinicians (16 radiologists and 12 surgeons) with varying years of experience in the management of unruptured intracranial ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Interventional neuroradiologists and neurosurgeons usually rely on variables like patient age, operative risk factors, aneurysm size, morphology, location, growth rate, and intra-aneurysmal flow patterns to support their decisions regarding UIA management. However, substantial disagreement between doctors on management of UIA has been recently reported 8,9,10 , which suggests that doctors are not absolutely or uniformly sure about their beliefs on the management of UIA.…”
Section: A Shared Decision-making Model Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventional neuroradiologists and neurosurgeons usually rely on variables like patient age, operative risk factors, aneurysm size, morphology, location, growth rate, and intra-aneurysmal flow patterns to support their decisions regarding UIA management. However, substantial disagreement between doctors on management of UIA has been recently reported 8,9,10 , which suggests that doctors are not absolutely or uniformly sure about their beliefs on the management of UIA.…”
Section: A Shared Decision-making Model Proposalmentioning
confidence: 99%
“…Because of the subjective desires of patients and the variable indications of doctors 8,9,10 , we do not believe that a shared decision-making classification system, as described above, could generate specific scientific hypothesis for randomized trials. Nevertheless, whether study's results could be influenced by shared decisions before enrollment in trials is unknown, and it has to be demonstrated.…”
Section: A Shared Decision-making Model Proposalmentioning
confidence: 99%
“…With cost containment being a national priority, 6 demonstrating the financial viability of new treatment options is crucial. [7][8][9][10][11][12][13][14][15][16][17] Several studies have analyzed the economic aspects of cerebral aneurysm interventions. [18][19][20][21][22][23] However, the generalizability of their findings is limited because most authors failed to adjust appropriately for measured or unmeasured confounders.…”
Section: Introductionmentioning
confidence: 99%
“…We ask, can you ever have ‘true’, idealized equipoise for all physicians and subjects involved even for a fleeting moment? These potential trials are anything but trivial and would definitely move the field forward, including randomized clinical trials comparing observation to treatment for unruptured aneurysms,14 the use of balloon guiding catheters in acute stroke,15 or the role of general anesthesia versus conscious sedation in acute stroke 16. One can effortlessly identify proponents on either end of the spectrum for each of these studies, and we need have no fear that we are being unethical by participating in a trial where patients are well-informed and the community of experts has not reached consensus.…”
mentioning
confidence: 99%